Optical properties of Eu3+ doped calcium sodium bismuth borosilicate glasses via melt quenching method - Nakka Praveenkumar; K.V. Madhuri; Anju Babu; D.V. Krishna Reddy (Next Materials)
In the current work, melt quenching was used to synthesize Eu2O3 doped 5CaF2+ 10NaF+ (6-x) Bi2O3+ 39B2O3+ 40SiO2 -x Eu2O3 glasses (x = 0.00, 0.1, 0.3, 0.6, 0.9, and 1.2 mol%). Various characterizations methods have been used to explore the produced glasses' structural and spectroscopic features. X-ray diffraction (XRD) is used to confirm that the glass sample is amorphous. Many structural groups found in the current glass system are visible in FTIR spectra. We looked at fluctuations in the optical characteristics of Eu3+ ions using the UV-Vis-NIR spectra. Emission bands in the visible range of 540–740 nm are apparent in luminescence spectra. At 577, 591, 612, 652, and 701 nm, emission peaks are linked to the 5D0→7F0, 1, 2, 3, and 4 transitions. The CIE chromaticity diagram, which shows color coordinates of x = 0.661 and y = 0.301, indicates that glass (x = 0.6) has the maximum emission intensity of all the glass samples.